Research on Mechanical and Electrical Properties of Cu-Ag Alloys Designed for the Construction of High Magnetic Field Generators - Kawecki, Artur; Sieja-Smaga, Eliza; Korzeń, Kinga; Majchrowska, Magdalena; Noga, Piotr (Journal of Casting & Materials Engineering, 2021)
The individual sections, wiring and construction of electromagnet windings responsible for strong magnetic field impulses may be one application for hypoeutectic Cu-Ag alloys. High electrical properties and mechanical properties (tensile strength, yield strength, impact strength) as well as high heat, fatigue and rheological resistance are required for these kinds of applications due to the unique nature of such operations (strong vibrations of high frequency and amplitude resulting from Lorenz forces and the possibility of significant and rapid heating from Jule’s heat). The limited solubility of copper and silver in the solid state enables the effective modification of the alloys’ microstructure through heat treatment and further shaping of their high mechanical and electrical properties via cold plastic working. The article presents the manufacturing of Cu-Ag alloys with the weight percent of Ag between 3 and 7 using the continuous casting process along with research on the physicochemical, mechanical and electrical properties of the obtained casts. The research on the amount of plastic deformation and its influence on the wire drawing process and the mechanical and electrical properties of the wires is also discussed. The temperature coefficients of resistance were defined in order to determine the temperature influence on the electrical resistance changes dynamics. The microstructural analysis was carried out in the as-cast state. The preliminary research conducted indicates that the obtained Cu-Ag alloys in the as-cast state exhibit a set of high mechanical and electrical properties. The prospective next stage of research includes the selection of favourable heat treatment parameters which would provide optimally modified microstructure of the alloys, as well as determining the deformation coefficients allowing for further increases in the mechanical and electrical properties.